"The Dose Makes the Poison": Informing Consumers About the Scientific Risk Assessment of Food Additives. Issue 1 (7th May 2015) - Bearth, Angela; Cousin, Marie‐Eve; Siegrist, Michael
Abstract : Intensive risk assessment is required before the approval of food additives. During this process, based on the toxicological principle of "the dose makes the poison, ˮ maximum usage doses are assessed. However, most consumers are not aware of these efforts to ensure the safety of food additives and are therefore sceptical, even though food additives bring certain benefits to consumers. This study investigated the effect of a short video, which explains the scientific risk assessment and regulation of food additives, on consumers' perceptions and acceptance of food additives. The primary goal of this study was to inform consumers and enable them to construct their own risk‐benefit assessment and make informed decisions about food additives. The secondary goal was to investigate whether people have different perceptions of food additives of artificial (i.e., aspartame) or natural origin (i.e., steviolglycoside). To attain these research goals, an online experiment was conducted on 185 Swiss consumers. Participants were randomly assigned to either the experimental group, which was shown a video about the scientific risk assessment of food additives, or the control group, which was shown a video about a topic irrelevant to the study. After watching the video, the respondents knew significantly more, expressed more positive thoughts and feelings, had less risk perception, and more acceptance than prior to watching the video. Thus, it appears that informing consumers about complex food safety topics, such as the scientific risk assessment of food additives, is possible, and using a carefully developed information video is a successful strategy for informing consumers.